The diffusion and reception of the ideas of economic liberalism in Greece during the period 1828-1837 - Μπαλόγλου Χρήστος Π. (SPOUDAI Journal of Economics and Business, 2001)
The purpose of this paper is to bring to light the existence of an economic literature in Greece, and the diffusion of economic ideas in the country from its establishment in 1828 until the foundation of the first Chair of Economics in 1837. These attempts of the diffusion of these ideas came either from Corais' circle in Paris or from the Principalities by Danube. Their common characteristic is that both attempts provided Jean Baptiste Say's works. JEL Classification: B11, B12